Kualitas Hidup Pada Pasien Diabetes Melitus Dengan Gangren Setelah Dilakukan Perawatan Luka Modern: Quality Of Life In Diabetes Mellitus Patients With Gangrene After Modern Wound Care - Tanoto, Wahyu; Purnamasari, Vela (Chakra Brahmanda Lentera Institute, 2026)
The quality of life will be compromised for individuals afflicted with gangrene. Gangrene is the tissue necrosis resulting from vascular obstruction or ischemia. Gangrene is treated with wound care, which consists of cleaning, treating, and sealing diabetic wounds using sterile procedures. The employed wound care technique is contemporary dressing, which utilizes the wet principle to expedite the healing process. Wound care must be conducted consistently. This study aimed to investigate the quality of life of diabetes mellitus patients with gangrene who received contemporary wound care at the Niscare Trenggalek Clinic. This study employed a quantitative descriptive methodology with a complete sampling strategy with 15 respondents. The whole sampling strategy employed solely the quality of life variable. A questionnaire served as the research instrument, and percentages were employed to analyze the findings. The study's results indicated that nearly half of the participants, namely 4 respondents (27%), experienced a middling quality of life, whilst the majority, including 11 respondents (73%), reported an excellent quality of life. The quality of life of patients with diabetic wounds (gangrene) can be influenced by a number of factors, including age, gender, education, occupation, income, marital status, length of suffering, number of wound treatments, and help during wound therapy. It is intended that patients with diabetes mellitus and diabetic wounds (gangrene) will recognize the benefits of modern wound care and will practice wound care on a regular basis to guarantee that the wound healing process proceeds smoothly and enhances their quality of life.